Neuroplastic and cognitive impairment in substance use disorders: a therapeutic potential of cognitive stimulation - Sampedro-Piquero, Patricia; Ladrón de Guevara-Miranda, David; Pavón-Morón, Francisco Javier; Serrano, Antonia; Suárez-Pérez, Juan; Rodriguez-de-Fonseca, Fernando; Santín-Núñez, Luis Javier; Castilla-Ortega, María Estela (Elsevier, 2019)
Drug addiction is a chronic and relapsing disorder in which repeated drug exposure compromises brain neuroplasticity. Brain areas normally involved in learning and goal- directed behaviors become corrupted, which may lead to cognitive deficits that coexist with other addiction symptoms and predict a worse treatment outcome. New learning experiences that are not motivated by drugs may improve both cognitive deficits and drug-induced symptoms by promoting adaptive neuroplastic changes that could alleviate or reverse those involved in addiction. The present review will focus on whether potentiating healthy cognitive function, either by formal cognitive training or non-drug related environmental experiences, could exert beneficial effects in the therapeutics of addiction. Although additional studies are needed, the available clinical and preclinical evidence suggests that cognitive stimulation may provide a valuable adjuvant intervention in drug addiction.
Author manuscript
Keywords: Neuroplasticidad; Neuroplasticity; Environmental enrichment; Cognitive training; Exercise; Executive function; Memory